Comparison of efficacy and safety of His-Purkinje system pacing versus cardiac resynchronisation therapy in patients with pacing-induced cardiomyopathy: protocol for a randomised controlled trial. Issue 8 (2nd August 2021) - Chen, Junjun; Cheng, Liting; Wang, Zefeng; Liang, Zhuo; Dong, Ruiqing; Hang, Fei; Chen, Jieruo; Wang, Xinlu; Wang, Ziyu; Du, Xiao; Zhang, Junmeng; Wu, Yongquan
Abstract : Introduction: Recent studies have shown that the His-Purkinje system pacing (HPSP) can achieve electrocardiomechanical synchronisation, and thus improve cardiac function. For patients with pacing-induced cardiomyopathy (PICM) who should be treated with pacemaker upgrade, the HPSP is a viable alternative to cardiac resynchronisation therapy (CRT). However, no randomised controlled trial has been performed to evaluate the efficacy and safety of HPSP in patients with PICM. The present study compared the efficacy and safety of HPSP with that of traditional CRT in the treatment of patients with PICM. Methods and analysis: This study is a single-centre, randomised controlled non-inferiority trial. This trial was carried out at the cardiac centre of Beijing Anzhen Hospital. A total of 46 patients with PICM who needed pacemaker upgrade treatment between January 2022 and December 2023 will be enrolled in this study. Patients will be randomised into an investigational group (HPSP) and a control group (CRT) at a 1:1 ratio. The primary outcome is the duration of QRS complex (QRS width), and the secondary outcomes are NT-proBNP (N terminal pro B type natriuretic peptide), C reactive protein, the number of antibiotics used, left ventricular ejection fraction, end systolic volume, end diastolic volume, the hospitalisation duration, the incidence of postoperative infection, pacemaker parameters (threshold, sensing and impedance), the 6-minute walking test, and quality of life (36-Item Short Form Survey scale), all-cause mortality, cardiovascular death, heart failure-related rehospitalisation rate, other rehospitalisation rates, major complication rates and procedure costs. Ethics and dissemination: This study has been approved by the Beijing Anzhen Hospital Medical Ethics Committee (No. 2020043X). Trial registration number: Chinese Clinical Trial Registry (ChiCTR2000034265).